2015
DOI: 10.1016/j.vetmic.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection in and circulation of Bluetongue virus among domestic ruminants in Madagascar

Abstract: So far, no published data was available concerning the circulation of Bluetongue virus (BTV) in Madagascar. During a survey on Rift Valley Fever, we were able to detect a virus belonging to BTV. Therefore, we conducted a study aiming at characterizing molecularly the BTV isolated and assess the importance of circulation of BTV in Madagascar. A total of 4393 sera from ruminants selected randomly by stratification and sampled in 30 districts of Madagascar were tested for BTV. Moreover, 175 cattle were followed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The prevalence of BTV nucleic acid observed in cattle and goats in both wet (7.3%) and dry (2.7%) seasons as compared to wildlife (0.4%), suggests that cattle and goats, unlike wildlife, play an important role in the maintenance of BTV in Zambia. These results support earlier assertions that cattle and small ruminants such as goats, are important reservoir hosts for BTV in Africa [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of BTV nucleic acid observed in cattle and goats in both wet (7.3%) and dry (2.7%) seasons as compared to wildlife (0.4%), suggests that cattle and goats, unlike wildlife, play an important role in the maintenance of BTV in Zambia. These results support earlier assertions that cattle and small ruminants such as goats, are important reservoir hosts for BTV in Africa [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…The seroprevalence (96.2%) of BTV in cattle from Lusaka and Central provinces was high, indicative of widespread exposure to infection. High seroprevalence (95.9%) has been previously reported in cattle from Madagascar [35]. The observed high seroprevalence in cattle from Zambia was possibly due to increased Culicoides activity since sampling was undertaken during the wet season.…”
Section: Discussionmentioning
confidence: 61%
“…Occurs in all biogeographic domains [ 85 , 108 ]. Zoophilic species (cattle, sheep, and poultry) [ 210 ] and involved in transmission of RVFV [ 181 ], Andasibe virus (ANDV) [ 85 ], Bluetongue virus (BTV) [ 4 ], and Wuchereria bancrofti [ 23 ]. In Africa, zoophilic species [ 114 ] and involved in transmission of Birao virus (BIRV) [ 45 ] and BABV [ 1 ].…”
Section: Presentation Of Malagasy Mosquitoesmentioning
confidence: 99%
“…Further north, in Kenya, 19 BTV serotypes have been isolated from sentinel cattle but clinical disease is not evident among the indigenous sheep [ 12 ]. A recent study in Madagascar revealed a very high prevalence of BTV serotype 2 in cattle and large distribution of the virus amongst domestic ruminants [ 13 ]. In 2003, the first outbreak of BTV (BTV-3) occurred in the neighbouring Island of La Reunion [ 14 ] and at least four serotypes (BTV-2, 17, 10 and 21) have been detected circulating in deer from Mauritius [ 15 ].…”
Section: Introductionmentioning
confidence: 99%